2016
DOI: 10.3390/s16050699
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Proximity Detection of Moving Targets Using a Large-Scale Planar Capacitive Sensor System

Abstract: A novel method for proximity detection of moving targets (with high dielectric constants) using a large-scale (the size of each sensor is 31 cm × 19 cm) planar capacitive sensor system (PCSS) is proposed. The capacitive variation with distance is derived, and a pair of electrodes in a planar capacitive sensor unit (PCSU) with a spiral shape is found to have better performance on sensitivity distribution homogeneity and dynamic range than three other shapes (comb shape, rectangular shape, and circular shape). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Since signal follows the minimum impedance path, the major signal component passes through the path at the gap-edge of the electrode 27 . Therefore, the area near the gap between two electrodes has a relatively large ratio of electric field variables 28 . At the same time, most of particle interferences falls at the top of the electrode.…”
Section: Resultsmentioning
confidence: 99%
“…Since signal follows the minimum impedance path, the major signal component passes through the path at the gap-edge of the electrode 27 . Therefore, the area near the gap between two electrodes has a relatively large ratio of electric field variables 28 . At the same time, most of particle interferences falls at the top of the electrode.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, three 2 Journal of Sensors 3 Journal of Sensors electrode-connecting types that result in comb-structure, adjacent two-rectangular configuration, and two-edge patterns have been investigated [12]. According to Ye et al, electrodes with a spiral shape perform well in terms of dynamic range and sensitivity distribution homogeneity compared to those with the other shapes [15]. In this work, electrodes are connected as a symmetric structure, depicted in Figure 2(a), to mimic the spiral shape.…”
Section: Methodsmentioning
confidence: 99%
“…A complete analytical solution is possible by solving the Laplace equation, but only for a few simplified problems [ 12 ]. In recent studies, it has been shown that simulations with the FEM are an appropriate technique to investigate individual sensor properties of real capacitive sensor geometries [ 21 , 22 ].…”
Section: Fem Simulation Of the Capacitance Of Parallel Plate Capacitormentioning
confidence: 99%